Efforts to Improve Learning Achievement Theme 2 Loving Plants and Animals Sub-Theme 1 Benefits of Plants for Human Life in Thematic Lessons by Applying Visual Learning Methods - Siti Rahmatun (International Journal Labs, 2023)
Thematic learning, as an integrated educational approach, engages students in a comprehensive learning experience across multiple subjects. This research delves into the implementation of thematic learning through a study titled